Tarik Menarik antara Desentralisasi dan Sentralisasi Kewenangan Pemerintah Daerah dalam Urusan Pertanahan - Elita Rahmi (Fakultas Hukum Universitas Islam Indonesia, 2009)
Indonesian government does not have “political will” in implementation local government in the land field based on authority principles.This problem can be seen from overlapping regulation in land’s field,on the one hand stipulated that land as local’s autority,on the other hand it still as central’s autority.This tension brings to effect more confflicts in indonesia. To solve the above problem,it needs regulations sincroization in the land field which regulater that land task is local governments authority,while central government only to do preventive and refresif,monitoring through making regulation,standard and norm that will become the rule of the game for local government in implementing the lands authority.Key words :land matter, decentralization, centralization, autorite